Diagnosis and Management of Central Congenital Hypothyroidism - Lauffer, Peter; Zwaveling-Soonawala, Nitash; Naafs, Jolanda C.; Boelen, Anita; van Trotsenburg, A. S. Paul (Frontiers in Endocrinology, 2021)
Central congenital hypothyroidism (CH) is defined as thyroid hormone (TH) deficiency at birth due to insufficient pituitary stimulation of an otherwise normal thyroid gland. The incidence of central CH is currently estimated at around 1:13,000. Central CH may occur in isolation, but in the majority of cases (60%) it is part of combined pituitary hormone deficiencies (CPHD). In recent years several novel genetic causes of isolated central CH have been discovered (IGSF1, TBL1X, IRS4), and up to 90% of isolated central CH cases can be genetically explained. For CPHD the etiology usually remains unknown, although pituitary stalk interruption syndrome does seem to be the most common anatomic pituitary malformation associated with CPHD. Recent studies have shown that central CH is a more severe condition than previously thought, and that early detection and treatment leads to good neurodevelopmental outcome. However, in the neonatal period the clinical diagnosis is often missed despite hospital admission because of feeding problems, hypoglycemia and prolonged jaundice. This review provides an update on the etiology and prognosis of central CH, and a practical approach to diagnosis and management of this intriguing condition.